Optical Characterization of Adulterants Stingless Bee Honey Samples Using Tunable Laser Source - Sayed Mohd Azman, Sharifah Nur Diani; Awang, Noor Azura (Enhanced Knowledge in Sciences and Technology, 2025)
The study focuses on the optical characterization of adulterants in stingless bee honey samples using a Tunable Laser Source (TLS) at a wavelength of 1540 nm. Stingless bee honey, a highly prized natural product, is frequently adulterated, demanding excellent detection techniques. This project investigates the use of (TLS) at a wavelength of 1540 nm for detecting. This wavelength was chosen because it interacts effectively with honey’s molecular components, allowing for the sensitive observation of changes in composition. When glucose corn syrup is added to honey, it changes its optical properties, such as refractive index and peak power, which the TLS can detect. The methodology set up the TLS system and testing of honey samples contaminated with glucose corn syrup at concentrations varying from 0%, 10%, 20%, 30%, 40% and 50%. The spectral data were analysed utilizing an Optical Spectrum Analyzer (OSA), and the peak power at 1540 nm was recorded for each concentration. A linear relationship was observed between the adulterant concentration and the peak power, with pure honey displaying the minimum peak power and elevated concentrations of glucose corn syrup leading to an increase in peak power. These results were additionally corroborated by refractive index measurements, which similarly aligned with the levels of adulteration. The findings illustrate the efficacy of the TLS in the detection and quantification of adulteration in stingless bee honey. The system adeptly recognized alterations in optical properties caused by glucose corn syrup, thereby offering a dependable and non-destructive method for the analysis of adulteration. This research highlights the potential of TLS for quality assurance in honey production.